2020
DOI: 10.1371/journal.pone.0232341
|View full text |Cite
|
Sign up to set email alerts
|

Are gamers better laparoscopic surgeons? Impact of gaming skills on laparoscopic performance in “Generation Y” students

Abstract: Background Both laparoscopic surgery and computer games make similar demands on eye-hand coordination and visuospatial cognitive ability. A possible connection between both areas could be used for the recruitment and training of future surgery residents. Aim The goal of this study was to investigate whether gaming skills are associated with better laparoscopic performance in medical students. Methods 135 medical students (55 males, 80 females) participated in an experimental study. Students completed three lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Both Sammut et al and Datta et al found the video game experience to be advantageous to laparoscopic performance. 42 , 43 Rosser et al analyzed laparoscopic surgical performance of 33 surgical residents with video game exercises and past video game experiences. 44 Video game experience of >3 hours per week correlated with 37% fewer errors and 27% faster completion.…”
Section: Discussionmentioning
confidence: 99%
“…Both Sammut et al and Datta et al found the video game experience to be advantageous to laparoscopic performance. 42 , 43 Rosser et al analyzed laparoscopic surgical performance of 33 surgical residents with video game exercises and past video game experiences. 44 Video game experience of >3 hours per week correlated with 37% fewer errors and 27% faster completion.…”
Section: Discussionmentioning
confidence: 99%
“…This could be the consequence of the associations between video games and improved complex hand-eye coordination and visual attention. 12,26 Extensive video gaming is thought to alter cortical network plasticity and affect other dissociated tasks resulting in reduced reaction times. 27 Reconstructing two-dimensional images into three-dimensional environments is integral to both videogames and laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A typical example is computer gaming which has been reported to increase laparoscopic baseline performance and response to training. 12 Gender has also been reported to affect initial performance, with male students seaming to outperform females in certain aspects such as speed. [13][14][15] A different factor is experience in playing musical instruments which requires advanced motor skills.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies underlined this, showing that gaming skills may be an advantage when learning laparoscopic surgery [ 44 ]. Gradl et al put forward the hypothesis that women have less opportunity to deal with visual-spatial tasks in their childhood development and socialization, and conclude this may prove disadvantageous [ 45 ].…”
Section: Discussionmentioning
confidence: 99%